Effectiveness of Health Education Using Video and Poster Media on Elderly Knowledge About Hypertension - Doan Pratama; Lily Herlinah; Tria Astika Endah Permatasari (Jurnal Ilmiah Ilmu Keperawatan Indonesia, 2024)
Background: The elderly, defined as individuals aged 60 years and above, have seen an increasing population due to advancements in healthcare but also face challenges such as hypertension. Hypertension, often referred to as "The Silent Killer," is becoming more common among the elderly due to physiological changes associated with aging. This condition, a leading cause of global cardiovascular diseases, heightens the risk of serious complications such as stroke and heart attack. Objectives: This study aims to determine the effectiveness of health education using video and poster media on the knowledge of the elderly about hypertension. Methods: This study employs a quasi-experimental design using a Nonequivalent Control Group Design method, where the experimental and control groups were not randomly assigned. A total of 32 samples were collected and divided into two groups (control and treatment). Data analysis included univariate, bivariate, and multivariate analyses. Results: The MANOVA test results indicated that the most influential variable affecting the respondents' knowledge level was education, with a p-value of 0.026. This value approaches 1, indicating that education has a stronger correlation compared to other variables. Conclusion: There is an effect of health education using video and poster media on the knowledge level of the elderly about hypertension.